Drinking Is Different! Examining the Role of Locus of Control for Alcohol Consumption - Marco Caliendo; Juliane Hennecke (Institute of Labor Economics (IZA), 2020)
Unhealthy behavior can be extremely costly from a micro- and macroeconomic perspective and exploring the determinants of such behavior is highly important from an economist's point of view. We examine whether locus of control (LOC) can explain alcohol consumption as an important domain of health behavior. LOC measures how much an individual believes that she is in control of the consequences of her own actions for her life's future outcomes. While earlier literature showed that an increasing internal LOC is associated with increased health-conscious behavior in domains such as smoking, exercise or diets, we find that drinking seems to be different. Using German panel data from the Socio-Economic Panel (SOEP) we find a significant positive effect of having an internal LOC on the probability of moderate and regular drinking. We suggest and discuss two likely mechanisms for this relationship and find interesting gender dierences. While social investments play an important role for both men and women, risk perceptions are especially relevant for men.
Keywords: I12; D91; 330; locus of control; alcohol consumption; health behavior; risk perception; social investment